LANGUAGE AS A REFLECTION OF THOUGHTS AND A COMMUNICATION TOOL IN GUIDANCE AND COUNSELING - Devi Alvionita Alindra, Devi; Ndruru, Bernad Ekarisman; Siregar , Feby Yoana (English Language Teaching Prima Journal (ELT), 2025)
The language that emerges in interactions between individuals reflects the close relationship between language and culture, which contributes to the mindset and behavior of individuals. As a means of expression, language not only functions as a means of communication, but also as a reflection of how a person understands the world around them. Language reflects an individual's identity, shapes thinking habits, and influences how individuals interact with others. In the realm of language psychology, language is seen as an important factor in building perceptions, emotions, and effective communication patterns. Language is not only limited to verbal aspects, but also includes nonverbal expressions that help shape communication in guidance and counseling. Counselors who are able to use language cohesively, coherently, accurately, and meaningfully will be more effective in building empathetic relationships with clients. In the counseling process, the language used by the counselor must be able to create a comfortable, supportive atmosphere, and encourage clients to express their thoughts honestly. Thus, language becomes the main tool in building healthy communication, directing clients towards better self-understanding, and helping them find solutions to the problems they face. This study will further explore how the language used by counselors and the language responses of clients can affect the effectiveness of communication in guidance and counseling services. This study will examine the strategy of using appropriate language in the context of education and language psychology, in order to optimize the interaction between counselors and clients and improve the quality of counseling services.